Genome-wide identification of the expansin gene family in netted melon and their transcriptional responses to fruit peel cracking - Hu, Yanping; Li, Yuxin; Zhu, Baibi; Huang, Wenfeng; Chen, Jianjun; Wang, Feng; Chen, Yisong; Wang, Min; Lai, Hanggui; Zhou, Yang (Frontiers in Plant Science, 2024)
Introduction Fruit cracking not only affects the appearance of netted melons (Cucumis melo L. var. reticulatus Naud.) but also decreases their marketability. Methods Herein, to comprehensively understand the role of expansin (EXP) proteins in netted melon, bioinformatics methods were employed to discover the EXP gene family in the melon genome and analyze its characteristic features. Furthermore, transcriptomics analysis was performed to determine the expression patterns of melon EXP (CmEXP) genes in crack-tolerant and crack-susceptible netted melon varieties. Discussion Thirty-three CmEXP genes were identified. Chromosomal location analysis revealed that CmEXP gene distribution was uneven on 12 chromosomes. In addition, phylogenetic tree analysis revealed that CmEXP genes could be categorized into four subgroups, among which the EXPA subgroup had the most members. The same subgroup members shared similar protein motifs and gene structures. Thirteen duplicate events were identified in the 33 CmEXP genes. Collinearity analysis revealed that the CmEXP genes had 50, 50, and 44 orthologous genes with EXP genes in cucumber, watermelon, and Arabidopsis, respectively. However, only nine orthologous EXP genes were observed in rice. Promoter cis-acting element analysis demonstrated that numerous cis-acting elements in the upstream promoter region of CmEXP genes participate in plant growth, development, and environmental stress responses. Transcriptomics analysis revealed 14 differentially expressed genes (DEGs) in the non-cracked fruit peels between the crack-tolerant variety ‘Xizhoumi 17’ (N17) and the crack-susceptible variety ‘Xizhoumi 25’ (N25). Among the 14 genes, 11 were upregulated, whereas the remaining three were downregulated in N17. In the non-cracked (N25) and cracked (C25) fruit peels of ‘Xizhoumi 25’, 24 DEGs were identified, and 4 of them were upregulated, whereas the remaining 20 were downregulated in N25. In the two datasets, only CmEXPB1 exhibited consistently upregulated expression, indicating its importance in the fruit peel crack resistance of netted melon. Transcription factor prediction revealed 56 potential transcription factors that regulate CmEXPB1 expression. Results Our study findings enrich the understanding of the CmEXP gene family and present candidate genes for the molecular breeding of fruit peel crack resistance of netted melon.